A Three-Component Model Based on Macropropagation Phenomena Approach for Complex Building Scattering - Mehdi Ait-Ighil; Fernando Perez-Fontan; Joel Lemorton; Frederic Lacoste; Christophe Bourga; Michel Bousquet (International Journal of Antennas and Propagation)
Multipaths represent a common predominant and uncontrolled component on channel impairments for all terrestrial and Land Mobile Satellite systems. Without restrictions w.r.t mobile terrestrial applications, the addressed multipath problematic in this paper is focused on Land Mobile Satellite applications where delayed signal replicas are highly impacting performances on communication systems while they induce strong positioning errors for navigation systems. The actual trend in propagation channel modelling is to improve the multipath characterisation and representation by using semideterministic and hybrid physical-statistical models into channel simulators instead of narrow-band empirical approaches. In this context, this paper presents a new simplified model, called 3CM (3-Component Model) to reproduce building scattering in an efficient way which strongly improves computation performances. This model is based on asymptotic methods, namely, PO (Physical Optics) which allows the 3CM to be frequency scalable, polarimetric, and dielectric materials oriented. Note that the proposed model and the retained approach can be integrated into more complex tools such as existing ray tracers. However, this issue is not discussed in this paper.